Potensi Formulasi Sediaan Sabun Padat Minyak Kelapa dengan Pengisi Kaolin sebagai Media Pembersih Najis Mughallazah - Panjaitan, Vera Diana; Sukeksi, Lilis; Iriany; Siswarni (Talenta Publisher (Universitas Sumatera Utara), 2020)
Qur'an explains najis mughallazah be purified using water as much as 7 times and one of which uses the ground. The addition of clay to the soap helps remove impure DNA attached to the surface of the skin. This study was conducted to determine the effect of an increase in the amount of kaolin and reaction temperature on water content and hardness of soap; determine whether the soap formulas meet the quality requirements of SNI and determine whether the soap formula capable of eliminating the derivatives pig DNA using PCR analysis method. The reaction was designed in 4 reaction temperatures (50ºC - 80ºC), the consistency of kaolin (10% - 20%), 35% NaOH concentration, reaction time 10 minutes and the stirring speed of 250 rpm. The results showed that all variations meet SNI standards. The best results were obtained in 15%; 50ºC and 17.5%; 60ºC. First, rinse the soap can eliminate DNA smeared unclean human hands. DNA washing using water and soap shows the remaining conventional PCR DNA electrophoresis. Kaolin solid soap formulation produced may eliminate DNA and meet the standard SNI 06-3532-2016.